Analisis Linguistik Sejarawi Terhadap Aspek Fonologi Dan Leksikal Bahasa Jakun Di Johor - Kasim, Mohamad Rozi (2019)
This study discusses the Jakun language spoken by Orang Asli Jakun in the state of Johor. The first objective of this study is to describe the phonemic system of two Jakun dialects. The second objective of this study is to elaborate the phonological process of two Jakun dialects. Accordingly, the third and fourth objectives of this study are to compare the basic vocabulary and determine the relationship between the two Jakun dialects, and then compare the two Jakun dialects with standard Malay language. The four objectives were achieved by using several major theories, namely segmental phoneme theory by Bloomfield (1992), rule order theory by Chomsky & Halle (1968) and lexicostatistics theory suggested by Swadesh (1955).